2021
DOI: 10.3389/fimmu.2021.645210
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine Inoculation Route Modulates Early Immunity and Consequently Antigen-Specific Immune Response

Abstract: Vaccination is one of the most efficient public healthcare measures to fight infectious diseases. Nevertheless, the immune mechanisms induced in vivo by vaccination are still unclear. The route of administration, an important vaccination parameter, can substantially modify the quality of the response. How the route of administration affects the generation and profile of immune responses is of major interest. Here, we aimed to extensively characterize the profiles of the innate and adaptive response to vaccinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 64 publications
1
36
0
Order By: Relevance
“…Most importantly, it involved a similar distribution of cell subsets, in contrast to the response to a second SC injection, which engaged more highly mature/activated cells that were induced long after the first administration of the vaccine (9). Thus, depending on the route of MVA administration, not only the Ab and T cells responses (8), and the early inflammatory/innate responses to the first immunization (Figures 2B, 3 and 5C, and as previously shown (8,9)) differed, but also the long-term impact on neutrophils (Figure 5C and as previously shown ( 9)).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Most importantly, it involved a similar distribution of cell subsets, in contrast to the response to a second SC injection, which engaged more highly mature/activated cells that were induced long after the first administration of the vaccine (9). Thus, depending on the route of MVA administration, not only the Ab and T cells responses (8), and the early inflammatory/innate responses to the first immunization (Figures 2B, 3 and 5C, and as previously shown (8,9)) differed, but also the long-term impact on neutrophils (Figure 5C and as previously shown ( 9)).…”
Section: Discussionmentioning
confidence: 98%
“…Animals were immunized twice, two months apart, with the ANRS recombinant MVA-HIV B vaccine (Transgene) at a dose of 4 x 10e 8 plaque forming units (PFU) by ID injections distributed over 10 injection points (150 μL/point of injections, all along the back, in two columns). Recombinant HIV-1 antigens consisted of the complete sequence of gag, fused to fragments from pol (residues 172-219, 325-383 and 461-519) and nef (residues 66-147 and 182-206) of the Bru/Lai isolate.…”
Section: Vaccine Immunization and Blood Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…We assessed the humoral response to confirm the efficiency of vaccination, as Abs are the main immune correlate of protection for most vaccines (16), including vaccinia virus (VACV) and MVA against smallpox (17). As previously shown (8), MVA was highly immunogenic after ID injection. It induced high levels of MVA-specific IgGs (Figure 1B).…”
Section: Mva Injected Id Induces a Strong Specific Humoral Responsementioning
confidence: 99%
“…The route of vaccine administration influences antigen/ adjuvant trafficking, local and systemic inflammation, innate effectors, and the resulting adaptive immune response (4)(5)(6)(7). We have shown that, like the antigen-specific antibody and Tcell responses, the early innate responses differ between subcutaneous (SC) and intradermal (ID) immunization, with the recruitment of distinct cell populations and activation of different immunomodulatory genes in skin and blood in response to a model live attenuated vaccine, Modified vaccinia virus Ankara (MVA), in non-human primates (NHPs) (8).…”
Section: Introductionmentioning
confidence: 99%